CONTAGIOUSNESS OF POLITENESS ON YOUTUBE - Cipto Wardoyo (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This study tries to shed a light on whether politeness strategies used in YouTube comment sections’ online discussion are contagious. Particularly, it explores the politeness strategies used in comments and replies from the three most popular videos in 2018 of “The Tonight Show Starring Jimmy Fallon” YouTube channel. By using a qualitative design with computer - mediated discourse analysis approach, this study confirms that politeness strategies used in the comment sections are contagious. It is also revealed that impolite strategies dominate the whole discussions even in funny content and the level of impoliteness increases as the degree of disagreement gets higher.